Defense rights and police investigation in the EU - Žunić Tijana; Đukić Tijana (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2012)
The abolition of the European borders has benefited a large number of people, allowing ordinary European citizens to move freely around and within the European Union. This, however, means that criminal organizations and terrorist groups have also gained their 'paradise'. Consequently, European attempts to combat crime had to overcome individual national actions by developing co-operation between the Member States. Police cooperation, as its integral part, was established on the bilateral and multilateral level. Nevertheless, the balance between strengthening of the police powers, on the one hand, and rights of individuals, on the other, has been disturbed. Has the EU overstepped the line and infringed basic human rights and fundamental freedoms, in particular considering right to privacy and defense of suspects? In order to find the answer the authors focused on the development of the police powers alongside the protection of the defendants' rights concerning three levels, i.e. national level of Member States, bilateral co-operation and multilateral co-operation in EU.